Strategi Kepemimpinan Kepala Sekolah dalam Mewujudkan Lingkungan Belajar Berkualitas melalui Pengelolaan Sarana Pendidikan - Alya Rohayati; Nur Zaidah; Binti Masrufa; Sunardi Sunardi (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2026)
This study aims to analyze the principal's managerial leadership strategy in managing infrastructure to create a quality learning environment at SMA Primaganda. The research focus covers three main stages: needs-based planning, management implementation, and evaluation and supervision strategies. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, vice-principal for infrastructure, teachers, and students, and supported by intensive field observations. The results show that: 1) Infrastructure planning is carried out in a participatory manner by applying a